2013
DOI: 10.1177/230949901302100303
|View full text |Cite
|
Sign up to set email alerts
|

Bicompartmental versus Total Knee Arthroplasty for Medial and Patellofemoral Osteoarthritis

Abstract: Short-term outcome of BKA and TKA was comparable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…However, the modular implant is time-and technique-demanding and requires a high level of surgical expertise due to the multiple instrumentation and orientations with the multiple implants. 18,19 An advantage of the monolithic implant is possibly easier implementation for the surgeon, but the survivorship is unacceptable. 15 Another potential solution is patient-specific customized monolithic implants which have promising early survivorship and short-term results.…”
Section: Discussionmentioning
confidence: 99%
“…However, the modular implant is time-and technique-demanding and requires a high level of surgical expertise due to the multiple instrumentation and orientations with the multiple implants. 18,19 An advantage of the monolithic implant is possibly easier implementation for the surgeon, but the survivorship is unacceptable. 15 Another potential solution is patient-specific customized monolithic implants which have promising early survivorship and short-term results.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical data on survivorship on both, modular (4)(5)(6)(7)(8) or non-modular (9)(10)(11) bicompartmental knee arthroplasty (BKA) is scarce and results especially with a monolithic femoral component have been disappointing. Cartier and Argenson reported on outcome of patellofemoral replacement partially in combination with medial UKA without specifying the results of this subset group (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…2014 [18] RCT I Monolith 25 25 60.3 58.3 28.8 30 1 m, 4 m, 1, 2 1 3 3 1 Tan et al. 2013 [14] Retrospective cohort IIB Modular 15 12 52 60 10:5 7:5 26 (4.2) 28.3 (4.9) 6 m, 1, 2 0 0 0 0 Shah et al. 2013 [15] Retrospective cohort IIB Modular 16 20 52.1 (6.4) 65.1 (7.5) 10:6 16:4 27.6 (4.4) 27.3 (3.8) 6 m, 1, 2 1 0 0 0 Morrison et al.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 6 studies were selected for inclusion in the meta-analysis, as shown in the PRISMA flow diagram ( Fig. 1 ) [13] , [14] , [15] , [16] , [17] , [18] . A kappa value of 0.9 was determined based on the selections of two reviewers (S. K. and H.…”
Section: Resultsmentioning
confidence: 99%